Chicken eggs, childhood stunting and environmental hygiene: an ethnographic study from the Campylobacter genomics and environmental enteric dysfunction (CAGED) project in Ethiopia - Kevin Louis Bardosh; Jeylan Wolyie Hussein; Elias Ahmed Sadik; Jemal Yousuf Hassen; Mengistu Ketema; Abdulmuen Mohammed Ibrahim; Sarah Lindley McKune; Arie Hendrik Havelaar (BMC, 2020)
Abstract Background Childhood stunting and malnutrition condemn millions of people globally to a life of disadvantage and cognitive and physical impairment. Though increasing egg consumption is often seen as an important solution for low and middle income countries (including Ethiopia), emerging evidence suggests that greater exposure to poultry feces may also inhibit child growth due to the effects of enteric bacteria, especially Campylobacter, on gut health. Methods In this rapid ethnographic study, we explored village poultry production, child dietary practices, and environmental hygiene conditions as they relate to Campylobacter risk and intervention in 16 villages in Haramaya Woreda, Eastern Ethiopia. Results In the study area, we found that women assumed primary responsibility to care for both chickens and children: in feeding, housing, and healthcare. Most chickens were free-range local indigenous breeds, and flock sizes were small and unstable due to epidemics, seasonal trends, reproductive patterns, and lack of food. Generally, eggs were seen as "too luxurious" to be eaten, and were predominantly sold at local markets for scarce cash, despite high malnutrition rates. Local narratives of extreme poverty, social dietary norms, parental fatalism, and lack of "dietary consciousness" (as it was called) were invoked to explain this. We found that homesteads were highly contaminated with human and animal feces. Although community members viewed chicken feces and poultry gastrointestinal contents as particularly noxious in comparison to other animals because of their feeding behaviour, they did not relate them to any particular disease. Shared human-animal housing and childcare practices place children at high risk of exposure to enteric bacteria from animal manure, despite daily routines designed to manage the domestic landscape. Conclusions Addressing childhood stunting and malnutrition through egg production in rural landscapes like Haramaya must navigate three distinct health and care regimes: for children, chickens, and home environments. Interventions should be based on a holistic approach to social and economic empowerment, one that considers both women and men and integrates nutrition, health, and community change as its overarching goal.